COMPARATIVE ANALYSIS OF TWO QUEUING SYSTEMS M/HE2/1 WITH ORDINARY AND WITH THE SHIFTED INPUT DISTRIBUTIONS - Tarasov, V. N.; Bakhareva, N. F. (Radio Electronics, Computer Science, Control, 2019)
Context. In the queueing theory, studies of particular systems of the M/G/1 type are relevant in that they are still actively used in the modern theory of teletraffic. The problem of finding a solution for the mean waiting time in a queue in the closed form of two systems with ordinary and shifted exponential and hypererlangian input distributions is considered. Objective. Obtaining a solution for the main system characteristic – for the average waiting time in a queue for two queuing systems of type M/G/1 and G/G/1 with conventional and offset exponential and hypererlangian input distributions. Method. To solve this problem, we use the classical method of spectral decomposition of the solution of the Lindley integral equation. This method allows to obtain a solution for the average waiting time for the systems under consideration in closed form. The method of spectral decomposition of the solution of the Lindley integral equation plays an important role in the theory of systems G/G/1. For the practical application of the results obtained, the well-known method of moments of probability theory is used. Results. Spectral decompositions of the solution of an integral equation of Lindley for couple of systems by means of which formulas for the average time of waiting in queue in the closed form are received. The shifted exponential distribution transforms the system M/G/1 into the system G/G/1. Conclusions. The spectral decompositions of the solution of the Lindley integral equation for the systems under consideration are obtained and with their help, the formulas for the average waiting time in the queue for these systems in a closed form are derived. These expressions expand and complement the known queuing theory formulas for the average waiting time for M/G/1 and G/G/1 systems with arbitrary laws of input flow and service time distributions. This approach allows us to calculate the average latency for these systems in mathematical packages for a wide range of traffic parameters. All other characteristics of the systems are derived from the waiting time. In addition to the average waiting time, such an approach makes it possible to determine also moments of higher orders of waiting time. Given the fact that the packet delay variation (jitter) in telecommunications is defined as the spread of the waiting time from its average value, the jitter can be determined through the variance of the waiting time. The method of spectral decomposition of the solution of the Lindley integral equation for the systems under consideration makes it possible to obtain a solution in a closed form and these solutions are published for the first time.